Solitary Ureteral Metastasis of Carcinoma Stomach : An Unusual Presentation (Bangladesh Journal of Urology, 2020)
Ureteral metastasis from gastric cancer is rare. It is usually diagnosed in the setting of an advanced gastric cancer or on postmortem examination. Isolated ureteral metastasis without involvement of other sites is extremely rare. We describe a 35-years age woman with gastric cancer and right ureteral metastasis. She presented with right flank pain due to right sided hydro-ureteronephrosis following ureteral obstruction. Surgical relief of the obstruction was sought and the surgical biopsy specimens showed metastatic adenocarcinoma in the ureteral wall. A search for the primary lesion revealed gastric cancer. She denied any symptoms referable to her upper GI tract.Bangladesh Journal of Urology, Vol. 21, No. 1, January 2018 p.40-42